Socialization Of Computer-Based Semester Exam System (CBT) - Siswanto; Hermawansa; Utami, Feri Hari; Alianse, Rizka Tri; Fredricka , Jhoanne (Jurnal Kewirausahaan dan Bisnis, 2019)
Information Technology, which is a technology in the field of computer science, is a type of field of science that always experiences many advances, both in data processing, image processing or a combination of the two. This happened because of the development of processor technology which is the main component of computer machines, where with the development of processor technology, software manufacturers also moved to follow the existing technology. Situation analysis of partners, obtained an illustration of the teacher's lack of understanding of the development of information technology, especially in terms of CBT-based semester exams. This is due to new assumptions about existing terms, therefore the school conveys the need for socialization of the intended technology directly to the teachers of SMA N 6 Bengkulu Tengah. Part of the field of computer science that continues to grow, such as artificial intelligence, which continues to try to make computer machines as tools and substitutes for functions carried out by humans. The progress shown by the ability of computers to serve users to search for education through internet facilities certainly requires its users to keep abreast of existing developments. The results obtained from these activities are the level of teacher interest in information technology knowledge which includes CBT-based exams which are shown by the enthusiasm of teachers in participating in activities